Energy Efficiency and Profitability Analysis in Sharia-Compliant Microenterprises Applying Green Business Principles - Devi Maya Sofa; Aning Fitriana; Chems Eddine Boukhedimi (International Forum of Researchers and Lecturers, 2024)
Microenterprises are crucial to the economic landscape, especially in developing countries, as they contribute significantly to GDP and employment. However, these businesses often face challenges in adopting sustainable practices due to financial constraints, limited resources, and market access issues. This research evaluates the impact of energy efficiency on the profitability of Sharia-compliant microenterprises applying green business principles. By integrating energy-saving measures, such as energy-efficient technologies and optimized consumption, microenterprises can reduce operational costs and improve profitability. Sharia-compliant businesses, which adhere to ethical and sustainable practices, tend to be more open to implementing such green practices. The findings show that energy-efficient microenterprises outperform conventional ones in profitability, as energy-saving leads to lower costs and enhanced competitiveness. The study also highlights the importance of green finance in supporting these enterprises by overcoming financial barriers, allowing them to adopt energy-efficient technologies. Despite the clear benefits, challenges such as high initial investment costs and limited access to efficient technologies remain. Policy intervention, including financial incentives and education, is necessary to address these barriers and enable microenterprises to fully capitalize on energy efficiency. In conclusion, energy efficiency is not only a key driver of profitability for Sharia-compliant microenterprises but also a strategy for long-term sustainability and competitiveness.